Creative accounting and financial performance of public listed companies in Malaysia / Mazurina Mohd Ali … [et al.] - Mohd Ali, Mazurina; Haron, Noor Hasniza; Othman, Nur Ain; Hasnan, Suhaily (Faculty of Accountancy, 2019)
Worldwide corporate failure has become one of major issue discussed related to excessive practice of creative accounting. Creative accounting inclusive of income smoothing is conducted with the intention to indicate company performance aligned with the companies’ objective. This empirical study is conducted with an objective to examine the relationship of creative accounting practices (measured by income smoothing and tax avoidance) and the impact of financial performance (measured using return of assets) of Malaysian public listed companies. Income smoothing and tax avoidance are some of the important element being discussed together with creative accounting practices and financial performance. This research is conducted by selecting 410 public listed companies in Bursa Malaysia by using purposive sampling. The secondary data was collected from data stream and from the information disclosed in website of the selected public listed companies. Descriptive and inferential statistics together with multiple linear regression technique were performed by using Statistical Package for Social Sciences Software (SPSS) to test variables under study. The result indicates that there is a positive relationship between income smoothing and return of assets (ROA) in Malaysian public listed companies. Agency theory is used to support the analysis and results of the research.